Understanding of the Lower Extremity Motor Recovery After First-Ever Ischemic Stroke. Issue 10 (17th June 2022) - Lee, Hyun Haeng; Sohn, Min Kyun; Kim, Deog Young; Shin, Yong-Il; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; Lee, So Young; Song, Min-Keun; Han, Junhee; Ahn, Jeonghoon; Lee, Young-Hoon; et al.
Abstract : Background: We aimed to verify the validity of the proportional recovery model for the lower extremity. Methods: We reviewed clinical data of patients enrolled in the Korean Stroke Cohort for Functioning and Rehabilitation between August 2012 and May 2015. Recovery proportion was calculated as the amount of motor recovery over initial motor impairment, measured as the Fugl-Meyer Assessment of Lower Extremity score. We used the logistic regression method to model the probability of achieving the full Fugl-Meyer Assessment of Lower Extremity score, whereby we considered the ceiling effect of the score. To show the difference in the prevalence of achieving the full Fugl-Meyer Assessment of Lower Extremity score between 3 and 6 months poststroke, we constructed a marginal model through the generalized estimating equation method. We also performed the propensity score matching analysis to show the dependency of recovery proportion on the initial motor deficit at 3 and 6 months poststroke. Results: We evaluated 1085 patients. The recovery proportions at 3 and 6 months poststroke were 0.67±0.42 and 0.75±0.39, respectively. A 1-unit decrease in the initial neurological impairment and the age at stroke onset increased the probability of achieving the full Fugl-Meyer Assessment of Lower Extremity score, which occurred at both 3 and 6 months poststroke. The prevalence of those who reach full lower limb motor recovery differs significantly between 3 and 6 months poststroke. We also found out that the recovery proportion at both 3 and 6 months poststroke is determined by the initial motor deficits of the lower limb. These results are not consistent with the proportional recovery model. Conclusions: Our results demonstrated that the proportional recovery model for the lower limb is invalid.